Smoke Release by Some Indian Woods and Wood Substitutes - Kumar, Rakesh; Kumar, A. Aravind; Bhawna (AMC Indian Journal of Civil Engineering, 2021)
This article presents the study of smoke release by some Indian woods and wood substitutes. These woods and wood substitutes are used in buildings as lining materials and furniture. The study will help to prepare fire retardant coating for interior lining materials, so the material will release nil/low smoke during fire after application of coating. Some tests were performed on Kail wood, Deodar wood, plywood, and fibre board to determine smoke release properties of these woods and boards. The SOD was determined using smoke density chamber as per ASTM E–662 which measures the amount of smoke released by a specimen in the burning (F–mode) or smoldering mode (NF mode). In smoldering mode, only radiation through a furnace of 2.5 W/cm2 was applied to the specimen surface. In flaming mode, radiation and fire from a burner were given to the specimen surface. The sample which represents the material was tested when it starts to smolder and again when a flame source was applied on the surface of specimen. The smoke density was between 0 (no smoke generated) to 800 as per standard ASTM E–662. The above said woods were tested as per standard in two modes, that is, NF and F-modes. The SOD was calculated for the above said materials to measure the amount of smoke release by materials.